(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The language and culture both are deeply rooted. A language cannot be understood completely without the knowledge of its cultural background. Similarly, a culture cannot be perceived comprehensively without its language. Therefore, language is not just about structures and words but there is a world inside any language and that world is known through its culture. This culture has always a crucial role to form its structure and impact in the particular language. This article will explain how Saadallah Wannous’s plays provide a suitable ground for both - communicative competence and discourse competence. Characters, plot, and settings open the world of Arabic language and Arab culture which can foster better understanding of cross cultural skills for a foreign language learner.